베트남의 사업협력계약 관련 법제 - 신충일(Shin, Choong-il) (Tonga pŏphak, 2018)
본고의 목적은 베트남의 사업협력계약에 관한 법제를 소개하는 것이다. 베트남 투자법은 베트남 내 다양한 투자형태 중 하나로 사업협력계약을 통한 투자를 규정하고 있으며, 이의 가장 큰 특징은 경제단체의 설립 없이 당사자간 계약에 따라 베트남 내에서 사업을 이행한다는 점이다. 외국인투자자가 참여하는 사업협력계약은 투자등록증의 발급이 요구되는 베트남 내 외국인투자의 한 형태이다. 사업협력계약의 외국인 당사자는 베트남 내에 운영사무소를 설립할 수 있으며, 운영사무소는 사업협력계약의 이행을 위한 범위 내에서 제한적으로 활동할 수 있다. 사업협력계약과 관련하여 당사자간 분쟁이 발생하는 경우, 외국인 당사자는 베트남 내 소송 혹은 국내외 중재를 통하여 이를 해결할 수 있다. 베트남은 뉴욕협약의 가입국이므로 원칙적으로 외국중재판정의 집행이 가능하며, 베트남 중재기관에 의한 중재판정은 베트남 법원의 판결과 동일하게 집행된다. 본고가 베트남 투자를 고려 중인 우리 기업이 사업협력계약 관련 법제를 이해하는데 도움이 되기를 기대한다. The purpose of this paper is to introduce the provisions of Vietnamese laws relevant to the Business Cooperation Contract (“BCC”). Vietnamese investment laws provide BCC as one of the various investment forms in Vietnam, and the most prominent feature of BCC is that the parties to it carry out business in Vietnam without establishment of economic organizations. However, it should be noted that BCC where a foreign investor is one of the parties is a form of foreign investment in Vietnam that requires Investment Registration Certificate to be issued by investment registration agency. A foreign party to BCC could establish an operating office in Vietnam, and such office could conduct business activities under the limited scope to implement BCC. If disputes arise from BCC, a foreign party could resolve such disputes by litigation at Vietnamese courts, as well as foreign or domestic arbitration. Since Vietnam is a member of the New York Convention, foreign arbitral awards are in principle implemented in Vietnam, and domestic arbitral awards are implemented the same as domestic court decisions. It is expected that this paper will help Korean companies considering investment in Vietnam understand the laws governing BCC. KCI Citation Count: 0